Strengthening the Rural Women's Entrepreneurship Spirit in Facing the Asean Economic Community (Da'wah in the Economic Context of Society) - Juli, Sabiruddin b (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
This article reports the results of a study on how to fill the free market program of ASEAN Economic Community (AEC). Indonesia has significant demographic bonus when compared to other ASEAN countries, so that specifically Indonesia will become an easy target for economic activity (read: free market flow transactions) carried out by all members of ASEAN. Demographic bonus is an opportunity and challenge for the Indonesian people, both for those who live in cities or in the countryside. This condition will be more complicated, if the mapping potential of the population does not become a serious concern for the government and stakeholders so that the people of Indonesia will become the largest consumer for products of ASEAN countries. One of the potential populations of Indonesia is women, because they have specific skills that are able to be directed towards an income. The purpose of this study is to prepare the people of Indonesia who have the skills, especially women in entering the AEC both urban and rural communities. This study uses a qualitative method of observation, interviews and review of documents, such as books, newspapers and others.